2017
DOI: 10.18203/2394-6040.ijcmph20171362
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and impact of early marriage on mother and her newborn in an urban area of Davangere: a cross-sectional study

Abstract: Background: Early marriage is a long established custom in India. In spite of the legislations prohibiting early marriages, the prevalence of child marriages in our country is 30.2%, with the highest prevalence in Rajasthan (35.4%) and lowest in Himachal Pradesh (0.5%).Thus, this study was undertaken to study the prevalence, determinants and impact of early marriage on the mother and her newborn in an urban area of Davangere. Methods: A cross-sectional study was conducted over a period of 6 months in the Urban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 4 publications
4
5
0
1
Order By: Relevance
“…Parents' educational level: 47.4% and 78.3% of participant's fathers and mothers were illiterate respectively (Table 1), similar to the reported 46% and 77% illiterate fathers and mothers in a study conducted in an urban Indian area among 900 participants [14].…”
Section: Discussionsupporting
confidence: 77%
“…Parents' educational level: 47.4% and 78.3% of participant's fathers and mothers were illiterate respectively (Table 1), similar to the reported 46% and 77% illiterate fathers and mothers in a study conducted in an urban Indian area among 900 participants [14].…”
Section: Discussionsupporting
confidence: 77%
“…12 Furthermore, in our study, the results have been found to be consistent with other studies primarily because poor families often tend to think that marrying their girl child early, will provide social and financial security to their daughters. 23 Cultural family structure, weak authority of females, and responsibility to fulfill needs, also forces parents of a girl child to marry their child at a younger age. 24 In our study, it was observed that husbands who were involved in labor as well as those having education till high school were more likely to marry females less than the national legal age for marriage.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that people with low incomes in Vietnam tend to be younger than people in middle- and higher-income families [13] . A study in India reported that literacy and socio-economic status of the mother and her parents were a major determinant in deciding the age at marriage [8] . A study also reported that poverty and poor education are underlying causes of child marriage, which is usually against the will of girls who desire to be educated [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that early marriage reduces the chances of the woman completing her education and thereby minimising her chances of earning a decent livelihood. This leads to a vicious cycle where poverty and low literacy levels are coupled with religious, social, and cultural influences which lead to a higher prevalence of early marriages [8] .…”
Section: Introductionmentioning
confidence: 99%